Enhancing mesenchymal stem cell survival and homing capability to improve cell engraftment efficacy for liver diseases - Yu, Shaoxiong; Yu, Saihua; Liu, Haiyan; Liao, Naishun; Liu, Xiaolong (Stem cell research & therapy, 2023)
Although mesenchymal stem cell (MSC) transplantation provides an alternative strategy for end-stage liver disease (ESLD), further widespread application of MSC therapy is limited owing to low cell engraftment efficiency. Improving cell engraftment efficiency plays a critical role in enhancing MSC therapy for liver diseases. In this review, we summarize the current status and challenges of MSC transplantation for ESLD. We also outline the complicated cell-homing process and highlight how low cell engraftment efficiency is closely related to huge differences in extracellular conditions involved in MSC homing journeys ranging from constant, controlled conditions in vitro to variable and challenging conditions in vivo. Improving cell survival and homing capabilities enhances MSC engraftment efficacy. Therefore, we summarize the current strategies, including hypoxic priming, drug pretreatment, gene modification, and cytokine pretreatment, as well as splenectomy and local irradiation, used to improve MSC survival and homing capability, and enhance cell engraftment and therapeutic efficiency of MSC therapy. We hope that this review will provide new insights into enhancing the efficiency of MSC engraftment in liver diseases.